User Comfort with the F-KICO (Fetal Kick Count) Tool and Its Correlation with Maternal Fetal Attachment: A Cross-Sectional Study - Yuni Purwati; Diah Nur Anisa; Nuzul Fathu Rohman; Norlaila Abu Samah (Jurnal Manajemen Informasi Kesehatan (Health Information Management), 2026)
Introduction: Fetal movement monitoring is an important component of antenatal care to support fetal well-being and contributes to achieving Sustainable Development Goals (SDG) 3: Good Health and Well-Being through improved maternal and fetal health. The F-KICO (Fetal Kick Count) model has been developed and validated through expert review; therefore, a pilot study was conducted to evaluate user comfort and its relationship with maternal fetal attachment (MFA). This study aimed to examine the correlation between user comfort in using F-KICO and MFA. Methods: A pilot cross-sectional study was conducted among 100 pregnant women recruited from four Public Health Centers in Bantul, Indonesia (Kasihan I, Kasihan II, Bantul II, and Sedayu II). User comfort was measured using the Fetal Movement Monitoring User Comfort Scale (FMM-UCS), while MFA was assessed using an adapted Prenatal Attachment Inventory (PAI). Data were analyzed using descriptive statistics, the Kolmogorov–Smirnov normality test, and Pearson correlation analysis. Results: Most participants reported good comfort in using the F-KICO tool and demonstrated good MFA. Pearson correlation analysis revealed a significant positive relationship between user comfort and MFA (r = 0.462, p < 0.01), indicating that higher comfort in using the monitoring tool was associated with stronger emotional bonding between mother and fetus. Conclusion: The F-KICO model demonstrated a high level of user comfort and was positively associated with MFA. These findings suggest that user-centered fetal movement monitoring tools can support maternal engagement and strengthen the MFA. The results also highlight the potential of F-KICO for further development and evaluation in larger populations.